Cultural Diplomacy, Cosmopolitanism and Global Hierarchy at the Shanghai Expo. (February 2015) - Winter, Tim
In 2010, the city of Shanghai hosted the largest and most spectacular World's Fair ever. Shanghai Expo attracted a staggering 73 million visitors, around 98% of whom were domestic Chinese, and involved the participation of 190 countries. As a forum of "virtual tourism, " the event is significant given the rapid and long-term growth in outbound Chinese tourism. This article pursues a closer reading of how "the world" was performed and exhibited to these visitors. Oriented by two theoretical considerations—the spatial configuration of the expo site and its cosmopolitan imagination—the article considers how the format of the Expo revealed and declared certain elements of the global, while simultaneously effacing and squeezing out others. The Expo is thus interpreted as an important mechanism in the creation of a new national citizenry in China and as part of the ceremonialization of a global polity of a "family of nations."